Thin, stretchable, universal wireless power transfer system for electric vehicle charging. Issue 58 (24th September 2020) - Guo, Yibing; Zhang, Han; Liu, Hao; Li, Shuang; Yin, Shizhen; Cao, Peng; Zhang, Lijuan; Ping, Xuecheng; Guo, Liang
Abstract : A novel stretchable wireless power transfer (SWPT) system is developed to integrate the receiving coil on the vehicle roof and hang the transmission coil over the vehicle to shorten the transmission distance and improve the power transfer efficiency. Abstract : Wireless power transfer technology has emerged as a new class of prospective components for electric vehicle charging. However, conventional wireless power transfer systems often suffer from unsatisfactory charging efficiency due to the comparatively longer recharge range and insufficient universality for various car models. Here, we present a stretchable wireless power transfer (SWPT) system that consists of thin and stretchable inductive coupling coils designed in serpentine shapes to provide stretchablility for the charging of any model. The receiving coil is adhered to the vehicle roof, and the transmitting coil hung over the vehicle is used to adjust the transmission distance. In order to improve the capability of coils, the design of windings is optimized to enhance stretchability and decrease the resistance via fabricating treble strand serpentine copper traces. The results show that the charging efficiencies of the SWPT remain stable even though the coils are under bending and stretching. As an application demonstration, the SWPT system is installed on the roofs of two different model cars, respectively, and the results demonstrate that the charging efficiencies remain stable. Thus, this work paves a novel way to develop a stretchable, convenient, universal, and high-performance wireless power transfer system.